Television and Very Young Children - DANIEL R. ANDERSON and TIFFANY A. PEMPEK (AMERICAN BEHAVIORAL SCIENTIST, Vol. 48 No. 5, January 2005 505-522, 2005)
The American Academy of Pediatrics (AAP) has recommended that children younger than 24 months of age not be exposed to television. Nevertheless, television programs and home videos are increasingly produced for very young children. This article reviews the extant research concerning television and very young children with respect to the AAP recommendation. More very young children are currently watching television than in the recent past; they pay substantial attention to TV programs and videos made for them. When learning from videos is assessed in comparison to equivalent live presentations, there is usually substantially less learning from videos. Although one study finds positive associations of language learning with exposure to some children's TV programs, other studies find negative associations of viewing with language, cognitive, and attentional development. Background TV is also a disruptive influence. Evidence thus far indicates that the AAP recommendation is well taken, although considerably more research is needed.